Developing the INGAME Model: Integrating Inquiry and Gamification to Enhance Creative Thinking in Elementary Students - Faridahtul Jannah; Shofia Hattarina; Didit Yulian Kasdriyanto; Ramadhan Kurnia Habibie (AL-ISHLAH: Jurnal Pendidikan, 2025)
The decline in creative thinking among elementary students presents a challenge to 21st-century education, particularly in systems dominated by rote learning. While inquiry-based learning fosters cognitive engagement and gamification enhances motivation, few instructional models integrate both to support creativity development. This study aimed to design, validate, and evaluate the INGAME model (Inquiry Model with Gamification Elements), which combines structured inquiry processes with game-based mechanics to enhance students’ creative thinking. Using the ADDIE framework, the model was developed through a research and development (RD) approach involving expert validation, teacher assessment, and classroom implementation. Data were collected from 23 fifth-grade students and analyzed through descriptive statistics and thematic analysis. Expert validation rated the INGAME model as very valid (M = 90.16%), and teacher assessments confirmed its practicality (M = 82%). Implementation results showed significant improvements in students’ creative thinking based on Torrance’s four indicators—fluency, flexibility, originality, and elaboration—with an average gain score of +1.13. Student engagement remained high throughout the model’s eight gamified inquiry phases, with observation data showing an average engagement level of 85.8%. The INGAME model demonstrates that integrating inquiry with gamification can foster creativity by aligning cognitive challenge with intrinsic motivation. It offers a structured, scalable, and teacher-friendly approach to cultivating creativity in elementary education while supporting broader educational reforms aligned with SDG 4.